Imaging Accessory Frame for Integration With an Operating Microscope (2015)
An accessory frame for selectively coupling components to an optical microscope for imaging of a subject is provided. The optical microscope has a body including an undercarriage. The accessory frame includes a mounting plate that attaches to the undercarriage of the microscope. The mounting plate includes a first attachment port and a second attachment port. The first attachment port is configured to couple a first optical assembly in an optical path of the microscope between an objective lens of the microscope and the subject. The second attachment port is configured to couple a second optical assembly to the microscope body with at least a portion of the optical path of the second optical assembly being outside of the optical path of the microscope.